NEST-BUILDING TERMITE ASSEMBLAGES IN A WHITE-SAND AMAZONIAN FOREST FRAGMENT, LORETO- PERU - ROJAS, Rommel R. (2025)
Termites are ecosystem engineers whose nest-building activities alter soil structure and nutrient cycling. In this study, we assessed the characteristics and diversity of nest-building termite assemblages in a white-sand forest fragment near Iquitos, Loreto, Peru. We surveyed ten 30 × 30 m plots in the forest to quantify nest density, taxonomic composition, nest-type, botanical substrates, nest coloration, and spatial variation in nest abundance. A total of 156 nests were recorded, representing five genera: Nasutitermes, Embiratermes, Coptotermes, Constrictotermes, and Termes. The most common botanical substrates associated with nest building belonged to the families Euphorbiaceae, Moraceae, and Fabaceae, particularly Alchornea triplinervia. Most nests were arboreal (58,0%) and dark brown in color (57,05%). Nest abundance increased significantly with greater distance from the road. In conclusion, despite the low nutrient availability, the white-sand forest fragment supports a dense and diverse assemblage of nest-building termites.